Distribution patterns and population structure of the blue shark ( Prionace glauca ) in the Atlantic and Indian Oceans - Rui Coelho; Jaime Mejuto; Andrés Domingo; Kotaro Yokawa; Kwang‐Ming Liu; Enric Cortés; Evgeny V. Romanov; Charlene da Silva; Fábio Hazin; Freddy Arocha; Aldrin Masawbi Mwilima; Pascal Bach; et al. (Fish and Fisheries, 2018)
The blue shark ( Prionace glauca ) is the most frequently captured shark in pelagic oceanic fisheries, especially pelagic longlines targeting swordfish and/or tunas. As part of cooperative scientific efforts for fisheries and biological data collection, information from fishery observers, scientific projects and surveys, and from recreational fisheries from several nations in the Atlantic and Indian Oceans was compiled. Data sets included information on location, size and sex, in a total of 478,220 blue shark records collected between 1966 and 2014. Sizes ranged from 36 to 394 cm fork length. Considerable variability was observed in the size distribution by region and season in both oceans. Larger blue sharks tend to occur in equatorial and tropical regions, and smaller specimens in higher latitudes in temperate waters. Differences in sex ratios were also detected spatially and seasonally. Nursery areas in the Atlantic seem to occur in the temperate south‐east off South Africa and Namibia, in the south‐west off southern Brazil and Uruguay, and in the north‐east off the Iberian Peninsula and the Azores. Parturition may occur in the tropical north‐east off West Africa. In the Indian Ocean, nursery areas also seem to occur in temperate waters, especially in the south‐west Indian Ocean off South Africa, and in the south‐east off south‐western Australia. The distributional patterns presented in this study provide a better understanding of how blue sharks segregate by size and sex, spatially and temporally, and improve the scientific advice to help adopt more informed and efficient management and conservation measures for this cosmopolitan species.